Prompt Engineering with ChatGPT - A Paradigm Shift in Education: A Guide for School teachers - Deshmukh, Narendra D; Shrouty, Vinita A (Indian Journal of Educational Technology, 2025)
Advancements in the area of Artificial Intelligence (AI) significantly impacted education in the era of the fourth industrial revolution. ChatGPT is an AI-powered application designed to generate chat responses in a conversational style, paving the way for flexible and responsive education to become mainstream. Various research on ChatGPT has sparked debates about its potential implications to support education for providing adaptive and personalized environments. This ongoing descriptive study analysed the use of ChatGPT by 24 school teachers who participated in a course in the first step of study. It aimed to evaluate teachers’ initial knowledge regarding ChatGPT, particularly its educational applications and potential advantages, before their course. Based on connectivism learning theory the present study sought to pinpoint effective prompts that teachers could incorporate into their teaching methods. Furthermore, it aimed to gauge the impact of the course on enhancing teachers’ awareness and understanding about ChatGPT, basically prompt engineering with its possible applications. The data was collected from base survey, feedback form, discussion forum and assignments and analysed using the descriptive method. The first step of the study revealed that teachers have minimal baseline knowledge of ChatGPT but after the course they found ChatGPT as their virtual teacher assistant. It emphasises the importance of preparing teachers for a paradigm shift in education. The study found a direct correlation between cognitive engagement and interaction levels of connectivism theory. However, as interaction levels increase, participant involvement tends to decline.